STUDY ON EFFICIENCY OF ROTATION-TRACTION-TECHNIQUE IN REDUCTION OF SHOULDER: A RANDOMIZED CONTROLLED CLINICAL TRIAL: Pharmaceutical Sciences-Medicine - HOSSEINI KASNAVIEH, MOHAMMAD; BASIR GHAFOURI, HAMED; MASOUMI, GHOLAMREZA; YASINZADEH, MOHAMADREZA; TAVAKOLI, NADER; AMIRI, HASSAN; KHATAMI, AMIR (International Journal of Life Science and Pharma Research, 2018)
The lack of accurate statistics in some methods about anterior shoulder dislocation, however we design a study for compare efficacy rotational with traction in patients.In randomized controlled trials, 111 participation’s divided randomized to two study group (rotational 56 and traction 55). This study was carried out in 2016 on Shohadaye 7tir Hospital in Tehran. Patients were following as complications, duration of the process and repeat or not to repeat dislocation. Duration of the process dislocation in rotational was lower compare to rotational, but is not significant p-value= 0.55. There was no difference statistically (p-value= 0.219) in replacing repeated anterior shoulder in traction (55%) with rotational (41%). did not differ in subclass for sex and age. There is not techniques anterior shoulder dislocation without error. So doctors have to learn different methods, in special clinical situations, overcrowded emergency condition, do the best and most appropriate method.